Analisis Kinerja Keuangan PT. Translingkar Kita Jaya - Suhartini; Pandoyo (JURNAL ILMU ADMINISTRASI PUBLIK DAN BISNIS, 2020)
This research study presents the phenomenon of financial performance at PT. Translingkar Kita Jaya 2011-2013. This study aims to determine the ability of the financial performance of PT. Translingkar Kita Jaya achieved during the year 2011 to 2013. The object of this research is on the financial statements of PT. Translingkar Kita Jaya for three years from 2011-2013. The data collection was done by using literature. The method used is a descriptive method using secondary data, by applying the techniques of financial ratio analysis through quantitative data. Research shows as follows: (1) Liquidity for three years from 2011 through 2013 showed excellent liquidity, which in 2011 amounted to 6.56 and increased to 23.56 in 2012 and increased again in 2013 by 29.41. (2) Solvency is not good that the company financed from external loans, which in 2011 amounted to 62% and in 2012 and 2013 by 59%. and (3) In Profitability ratios, showing the company for three years has not been able to make a profit, which means the company is still a loss. Conclusions ; (1) Maintaining the liquidity of the company and use funds more profitable. (2) The company that understands the needs of the company's capital and reduces the amount of spend. and (3) Increase revenues and reduce the load so that the company can improve profits